Russia and the Information Revolution - Peterson, D. J. (RAND Corporation, 2005)
This work, the result of a six-year study, sheds light on Russia's role in the global Information Revolution. It examines Russia's increasing reliance on information and communications technologies (IT) to improve its government institutions, modernize business and industry and stimulate economic growth, broaden information access, and enhance the quality of life for Russian people. The author examines Russia's emerging IT sector, how businesses in Russia are seeking to use IT to enhance productivity and profitability, the impact of IT on government, and the course of the Information Revolution in Russian society.